Medical Treatment and Dose Estimation of a Person Exposed to Tritium - Weibo Chen; Houwen Li; Kongzhao Wang; Huahui Bian; Youyou Wang; Fengmei Cui; Yulong Liu; Qiu Chen (SAGE Publishing, 2019)
In this study, we aimed to investigate the damaging effects and clinical therapy of internal contamination with tritium to provide information and gain experience for medical treatments in case of an emergency due to a nuclear accident. Histories were taken by several doctors who observed and recorded the clinical symptoms of the patient described herein. The general health situation was evaluated by laboratory and equipment analyses. Tritium concentrations in the urine were estimated according to relevant standards during the monitoring period using a liquid scintillation counting method. Clinical observation revealed that the patient had symptoms of mild asthenia and sleep disorder with improvement after appropriate treatment. The last committed effective dose was determined through measurement of the urine tritium concentration and dose estimation and was estimated to be 0.123 mSv; the total effective dose was 14.536 mSv. The medical treatment and dose estimation in this patient with tritium contamination were successful and can provide a reference for similar cases in the future.